DIFICULDADES ÀS DISCUSSÕES SOCIOCIENTÍFICAS EM AULAS DE CIÊNCIAS: CONTRIBUTOS DE TEXTOS ENUNCIATIVOS PRESENTES EM ITENS DE QUÍMICA DO ENEM (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
Socio-scientific Issues (SSI) cover controversies on social issues related to current scientific knowledge. The present work aimed to find alternatives for the development of SSI discussions within the classroom based on the chemistry items included in the National High School Exams tests, in the editions from 2014 to 2016. The results indicate that the selected items and Analyzed in this work have the potential for SSI discussions, since it is possible to associate subjects present in them that can lead the student to reflections relevant to scientific and social issues. There are still many challenges to its implementation in science classes, but these have been overcome as research on the subject advances and points out alternative ways of allowing the school to be a legitimating space for educational actions aimed at citizenship education.
Keywords: Socio-Scientific Issues; Nacional Exam; Teacher Training; Chemistry Training